INNOVATION OF THE USE OF HONEY AS A TOPICAL MEDICINE TO THE THERAPY OF ABDOMEN'S INCISION POST-CESAR - Muhammad Rizki Darmawan; Nur Mahampang; Dwi Lisa Nur'aini (International Islamic Medicine Forum, 2020)
Honey has long been used as food and medicine. One of the many researched benefits of honey is that it speeds up wound healing. The Koran and the hadiths clearly state that there is healing in honey. Along with advances in technology, cesarean delivery is increasingly being performed to help facilitate labor under various indications. However, cesarean delivery can limit the mother's activities in the care of herself and her child. On the other hand, cesarean delivery also often causes obstetric complications such as puerperal infection, endometritis, wound complications, and surgical healing complications. It will increase the cost of cesarean delivery. The authors reviewed the data regarding the effectiveness of honey in the therapy of post-cesarean delivery abdominal incisions. The data show that the antibacterial, anti-inflammatory, and antioxidant characteristics of honey can significantly affect the therapy of cesarean delivery incisions. The combination of the osmotic effect and hydrogen peroxide activity in honey can inhibit bacterial growth, reduce edema, exudate, and pain due to inflammatory processes. Besides, honey has the effect of protecting antioxidant enzymes from free radicals and reducing oxidative stress to reduce cell damage. Honey can also stimulate angiogenesis, the proliferation of fibroblasts and epithelial cells, and granulation, helping speed up the healing process. This paper discusses honey's mechanism in accelerating wound healing and its effect in preventing wound infection from improving the quality of health and the relationship between mother and child after cesarean delivery.